Pacritinib demonstrates spleen volume reduction in patients with myelofibrosis independent of JAK2V617F allele burden - Tremblay, Douglas (Blood Adv, 2020)
Myelofibrosis (MF) has heterogeneous clinical manifestations, with some patients exhibiting a myelodepletive phenotype characterized by cytopenias and an absent or low JAK2V617F allele burden. Ruxolitinib may be less effective in these patients. We assessed the efficacy of pacritinib, a JAK2/IRAK1 inhibitor, in MF patients with low JAK2V617F allele burden. In this post hoc analysis of the PERSIST-1 and -2 trials, patients with MF randomized to pacritinib or best available therapy (BAT) were stratified by JAK2V617F allele burden quartile for spleen response of ≥35% and improvement in total symptom score of ≥50%. Five hundred thirty-six patients were included. Patients with lower JAK2V617F allele burden had smaller baseline spleens and lower hemoglobin and platelet counts as compared with higher allele burden patients. Among pacritinib-treated patients, spleen responses were observed across all JAK2V617F allele burden quartiles and in JAK2V617F(−) disease. No spleen responses were observed among BAT-treated patients with allele burden ≤50% or JAK2V617F(−) disease. The intention-to-treat response rate was significantly higher on the pacritinib arm for JAK2V617F(−) disease (23.0% vs 0%; P = .033), and for the lowest allele burden quartiles (0%-25%: 20.9% vs 0%, P < .001; 25%-50%: 15.4% vs 0%, P = .020). There were significantly more symptom responders with pacritinib vs BAT in the 0% to 25% and 25% to 50% cohorts. Pacritinib treatment led to superior spleen and symptom burden reduction compared with BAT in patients with absent or low JAK2V617F allele burden, suggesting that pacritinib may be uniquely suited for patients with myelodepletive MF.